A Masked Form of an O‐Borylated Breslow Intermediate for the Diastereoselective FLP‐Type Activation of Aldehydes. Issue 10 (25th January 2022) - Fajardo, Angelica Mejia; Queyriaux, Nicolas; Camy, Aurèle; Vendier, Laure; Grellier, Mary; del Rosal, Iker; Maron, Laurent; Bontemps, Sébastien
Abstract: Breslow intermediates are very often elusive species whose application in frustrated Lewis pair (FLP) chemistry is unprecedented. Described herein is the use of a masked form of an O‐borylated Breslow (OBB) intermediate that performs FLP‐type activation of the carbonyl function of five different benzaldehyde derivatives with complete diastereoselectivity. The resulting compounds are characterised in solution by NMR spectroscopy (compounds 4 –8 ) and in solid state by X‐ray diffraction analysis (compounds 4 –6 ). A combined kinetic and theoretical investigation reveals the associative nature of the rate determining step and suggests that the OBB intermediate part is never released during the whole process. Abstract : Compound 3 featuring an FLP‐type activated CO2 is used as a masked form of an elusive O‐borylated Breslow intermediate for the complete diastereoselective FLP‐type activation of aldehydes. Kinetic and theoretical investigations shed light on the mechanism at play.